2021
DOI: 10.3389/fgene.2021.672433
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Avian Eggshell Biomineralization Protein Toolkit – New Insights From Multi-Omics

Abstract: The avian eggshell is a remarkable biomineral, which is essential for avian reproduction; its properties permit embryonic development in the desiccating terrestrial environment, and moreover, are critically important to preserve unfertilized egg quality for human consumption. This calcium carbonate (CaCO3) bioceramic is made of 95% calcite and 3.5% organic matrix; it protects the egg contents against microbial penetration and mechanical damage, allows gaseous exchange, and provides calcium for development of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 153 publications
0
24
0
Order By: Relevance
“…Thus, it is possible that there is insufficient variation in the phenotype for evolution to act effectively upon. However, we suggest that this is not the case due to the wealth of other studies that have demonstrated evidence for the evolution of eggshell thickness in avian and non-avian egg laying species 50 52 . Another point to consider is whether the co-evolutionary interactions between hosts and cuckoos in our study are sufficiently strong to select for changes to eggshell thickness.…”
Section: Discussionmentioning
confidence: 78%
“…Thus, it is possible that there is insufficient variation in the phenotype for evolution to act effectively upon. However, we suggest that this is not the case due to the wealth of other studies that have demonstrated evidence for the evolution of eggshell thickness in avian and non-avian egg laying species 50 52 . Another point to consider is whether the co-evolutionary interactions between hosts and cuckoos in our study are sufficiently strong to select for changes to eggshell thickness.…”
Section: Discussionmentioning
confidence: 78%
“…It is also expressed in hen digestive tract (172). Chicken OCX-36 is encoded by the BPIFB3 gene; its protein sequence shares 20-25% sequence homology to mammalian proteins associated with the innate immune response, such as lipopolysaccharide-binding proteins (LBP), bactericidal permeability-increasing protein (BPI) proteins and palate, lung and nasal epithelium clone (Plunc) family proteins and is involved in lipid binding functions (173,174). It displays lipopolysaccharide and lipoteichoic acid binding activity, suggesting its role as a pattern recognition molecule, which binds bacterial endotoxins in order to eliminate pathogens such as Staphylococcus aureus (31).…”
Section: Eggshell Specific Proteinsmentioning
confidence: 99%
“…Ovocleidins (OC-17, OC-116) are mainly secreted in hen uterine fluid during the active calcification stage of shell formation (14,168). Ovocleidin-116 (OC-116; MEPE, matrix extracellular phosphoglycoprotein, is the mammalian ortholog) is a major component of the chicken uterine fluid and is the most abundant matrix protein in the eggshell (14,174). Ovocleidin-17 is a phosphorylated protein with a C-type lectin (CTL) domain, which exhibits bactericidal activity against both Gram-positive and Gram-negative bacteria including Bacillus subtilis, Staphylococcus aureus, and Pseudomonas aeruginosa (175).…”
Section: Eggshell Specific Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the surface of an uncalcified eggshell membrane, calcified and mineralized shell layers are formed in the order of the mammillary layer, the palisade layer, the vertical crystal layer, and the outermost cuticle layer [ 12 ]. There are several factors affecting eggshell strength across different avian species, such as the egg weight and the crystallographic orientation of the mineralized eggshell [ 13 , 14 ]. Because the same species have the same crystallographic orientation, however, eggshell thickness is a main factor affecting eggshell strength [ 15 ].…”
Section: Introductionmentioning
confidence: 99%